Mercury in Amazonian fish from Madeira River basin, Rondonia state, Brazil - Gali, PAS; Bonotto, Daniel Marcos [UNESP]; da Silveira, E. G.; Bastos, W. R. (Wit Press, 2005)
This investigation was carried out at the Madeira River basin, located in the state of Rondonia, Brazilian Amazon. Fish from Madeira, Jaciparana, and Jamari rivers between 7 and 11 degrees parallels south and between 62 and 65 degrees meridians west in Rondonia state, Brazil, were sampled and chemically analyzed for mercury in order to evaluate if the inputs of this metal into the food-chain is occurring in levels reaching values above those recommended by the World Health Organization. This is because such an element is very dangerous when ingested by humans and its presence was extensively identified some years ago in the area, since it was utilized as an amalgam in processes for recovering alluvial gold.
Keywords: mercury; fish; statistical distribution; Madeira River basin; health hazard